PEDAGOGICAL ASPECTS OF CLOUD COMPUTING (Journal of Information Technologies in Education (ITE), 2011)
Recent progress in computer science in the field of redundancy and protection has led to the sharing of data in many different repositories. Modern infrastructure has made cloud computing safe and reliable, and advancement of such computations radically changes the understanding of the use of resources and services. The materials in this article are connected with the definition of pedagogical possibilities of using cloud computing to provide education on the basis of competence-based approach and monitoring of learners (students).
Keywords: Cloud computing; competence-based approach; competence-based tasks; Internet services; learning environment; monitoring of learning; pedagogical possibilities; Web-2 technologies